Complementary analytical platforms of NMR spectroscopy and LCMS analysis in the metabolite profiling of Isochrysis galbana - Ahamad Bustamam, Muhammad Safwan; Pantami, Hamza Ahmed; Azizan, Awanis; Shaari, Khozirah; Chong, Chou Min; Abas, Faridah; Nagao, Norio; Maulidiani, Maulidiani; Banerjee, Sanjoy; Sulaiman, Fadzil; Ismail, Intan Safinar (Multidisciplinary Digital Publishing Institute, 2021)
This study was designed to profile the metabolites of Isochrysis galbana, an indigenous and less explored microalgae species. 1H Nuclear Magnetic Resonance (NMR) spectroscopy and Liquid Chromatography-Mass Spectrometry (LCMS) were used to establish the metabolite profiles of five different extracts of this microalga, which are hexane (Hex), ethyl acetate (EtOAc), absolute ethanol (EtOH), EtOH:water 1:1 (AqE), and 100% water (Aq). Partial least square discriminant analysis (PLS–DA) of the generated profiles revealed that EtOAc and Aq extracts contain a diverse range of metabolites as compared to the other extracts with a total of twenty-one metabolites, comprising carotenoids, polyunsaturated fatty acids, and amino acids, that were putatively identified from the NMR spectra. Meanwhile, thirty-two metabolites were successfully annotated from the LCMS/MS data, ten of which (palmitic acid, oleic acid, α-linolenic acid, arachidic acid, cholesterol, DHA, DPA, fucoxanthin, astaxanthin, and pheophytin) were similar to those present in the NMR profile. Another eleven glycerophospholipids were discovered using MS/MS-based molecular network (MN) platform. The results of this study, besides providing a better understanding of I. galbana’s chemical make-up, will be of importance in exploring this species potential as a feed ingredient in the aquaculture industry.